PELIMPAHAN HAK ASUH ANAK KEPADA BAPAK MENURUT UU NO 1 TAHUN 1974 TENTANG PERKAWINAN - Hendrew Steven (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
AbstractMan as a social being is never out of burden with another human being. Humans have different interests with each other. With this difference of importance the relationship built between one human being and another can be the cause of conflict, disagreement, dispute, even hostility.The child is God's message for both his parents, society, nation and state as the heir of the teachings of Islam, the child receives every engraving and all direction given toThe child is a mandate, then taking care, nurturing, educating is the duty of the parents, so that the child has a good soul and berlaklak noble.